Principles and practice of constraint programming-- CP 2011 17th International Conference, CP 2011, Perugia, Italy, September 12-16, 2011, proceedings - Lee, Jimmy (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 17th International Conference on Principles and Practice of Constraint Programming, CP 2011, held in Perugia, Italy, September 12-16, 2011. The 51 revised full papers and 7 short papers presented together with three invited talks were carefully reviewed and selected from 159 submissions. The papers are organized in topical sections on algorithms, environments, languages, models and systems, applications such as decision making, resource allocation and agreement technologies.